Feedback and motor skill acquisition using a haptic dental simulator. (21st June 2016) - Al‐Saud, L. M.; Mushtaq, F.; Allsop, M. J.; Culmer, P. C.; Mirghani, I.; Yates, E.; Keeling, A.; Mon‐Williams, M. A.; Manogue, M.
Abstract: Aim: To investigate the effect of qualitatively different types of pedagogical feedback (FB) on the training, transfer and retention of basic manual dexterity dental skills using a virtual reality (VR) haptic dental simulator. Methods: Sixty‐three participants (M = 22.7 years; SD = 3.4 years), with no previous dental training, were randomly allocated to one of three groups ( n = 21 each). Group 1 received device‐only feedback during the training phase, that is the visual display of the simulator (DFB); Group 2 received verbal feedback from a qualified dental instructor (IFB); and Group 3 received a combination of instructor and device feedback (IDFB). Participants completed four tasks during which feedback was given according to group allocation as well as two skills transfer tests. Skill retention was examined immediately after training, at 1 week and at 1 month post‐test. Results: Statistically significant differences were found between the groups in overall performance ( P < 0.001) and error ( P = 0.006). Post hoc comparisons revealed the IDFB group produced substantially better performance and fewer errors in comparison with DFB and IFB training. This difference translated to improved performance in skill retention and generalisation of knowledge to novel tasks. Conclusion: These data indicate that the acquisition and retention of basic dental motor skills in novice trainees is best optimised through a combination of instructor and visual display (VR)‐driven feedback. The results have implications for the utility and implementation of VR haptic technology in dental education.